O diálogo platônico multifacetado: uma análise do Lísis em seus aspectos dramático, filosófico e comunicacional - Balog, Gabriel Bellemo (2023)
This dissertation analyzes Plato's Lysis as a multifaceted object, whereas delineating the deepening of three aspects of the dialogue. The objective of understanding the existing bridges between different dimensions of a platonic dialogue is justified due to the labeling of the Lysis as a “philosophical failure”, a perspective that has changed, in recent decades, as new researches investigate different spheres of the work in parallel with the logical-argumentative one. In a dramatic aspect, I focused on the scenic, theatrical, attributes of the Lysis. It was observed that its scenario evokes symbolisms of receptivity and competition, while its central characters represent essential concepts to the philosophical development of the work. As for the relationships established between these figures, they seem to strain the association between the concepts of eros and philia. In its philosophical sphere, focus was placed on the logical-argumentative path followed, in order to elucidate hypotheses and conceptual problems, and suggest a mapping of the arguments. While, in the first investigation of the dialogue, Socrates refutes Lysis regarding his ideas about freedom, knowledge and love; in the second, with Menexenus present, they explore the nature of the friend (philon), questioning what grounds the relationship of philia. Finally, in a communicational dimension of the Lysis, its dialectical-discursive mode and the intended objective of the characters’ dialogue was highlighted. I made a review on the form of the socratic dialogue and a study of the elenkhos: the preparation for it, its activation and its immediate aporetic results. After that, we faced the ethical function of Socrates' communication, the work’s implicit intention to the elentic and aporetic potencies that possibly aim at the leading of the soul (psychagogia) and the exhortation of his young interlocutors. From this analysis, it was possible to see how the Lysis can be understood as a multifaceted object, in which its aspects are inseparably articulated. A precise dramatic context supports a fruitful philosophical investigation, which takes on a more complete meaning under communicational attributes of Plato's text. Such bridges between the facets of the dialogue consolidate it as a unified work, but holder of multiple potencies, achieved at different levels of reading